The impact of quantitative and semi-quantitative culture of respiratory tract secretions on clinical decisions in a patient with suspected pneumonia - case study - Kamila Kasprzycka; Marcin Węglarz; Martyna Lewkowicz; Gracjana Ratuszny (Kazimierz Wielki University, 2023)
Pneumonia is one of the most common disease entities treated in the Intensive Care Unit. The standard diagnostic procedure for patients with suspected pneumonia is to evaluate the presence of symptoms of infection, physical examination, imaging, laboratory and microbiological tests, arterial blood gasometry and culture of respiratory tract secretions. In many Intensive Care Units, the preferred method of collecting material from the lower respiratory tract is an endotracheal aspirate. However, its semi-quantitative culture does not distinguish respiratory tract colonization from infection. Samples obtained by bronchoscopy are believed to be more representative of the presence of true pathogens in the lungs. An 87-year-old patient with myasthenia gravis was admitted to the Intensive Care Unit for suspected pneumonia. Laboratory tests showed elevated inflammatory markers and a chest X-ray showed interstitial densities in the left lower lobe. The result of semi-quantitative culture of tracheal aspirate was heavy growth of Staphylococcus aureus and heavy growth of Pseudomonas aeruginosa. The result of the quantitative BAL culture was S.aureus MSSA 105 colony-forming unit (CFU) per ml, Pseudomonas aeruginosa 102 CFU/ml. To consider a microorganism responsible for infection, the number of bacteria cells must exceed a designated threshold. For BAL it is ≥104 CFU/ml, for TA it is ≥106 CFU/ml, for PSB it is ≥ 103/ml. In this case, the cutoff point for identifying the pathogen responsible for the infection was reached only by Staphylococcus aureus (105 CFU/ml), not by Pseudomonas aeruginosa (102 CFU/ml). The final diagnosis was left-sided PN1 pneumonia of S.aureus etiology. A cloxacillin was used for the treatment. Clinical improvement was achieved. The described case proves the advantage of quantitative culture over semi-quantitative culture of respiratory tract secretions. The advantage of bronchoalveolar lavage over tracheal aspirate is also noticeable.